Pelatihan Pembuatan Media Pembelajaran (Pembuatan Soal-Soal) Menggunakan Powerpoint, Wondershare Quiz Creator Dan Edmodo Di SMK Apipsu Medan - Ikhsan Parinduri; Siti Nurhabibah Hutagalung (JPM: Jurnal Pengabdian Masyarakat, 2022)
Learning Media is very important for the continuity of the learning and teaching process. Making questions using application software and digital media. The form of the questions depends on the design, input and desired output. Some of the obstacles at the Medan APIPSU school are how to improve the quality of teachers in making questions both online and offline. The training is carried out in answering existing problems in improving the quality of development teachers in making questions and question banks in the form of essays, multiple choice, pictures and videos. The use of several Microsoft Powepoint, WondershareQuiz Creator and Edmodo features helps in carrying out these activities.